THE ECONOMIC IMPACT AND ADOPTION RATE OF DIGITAL FARMING ADVISORY PLATFORMS AMONG SMALLHOLDER FARMERS IN INDONESIA A SURVEY STUDY - Nahri Idris; Cedric Butler; Sarah Al-Jabri (Techno Agriculturae Studium of Research, 2025)
Digital Farming Advisory Platforms (DFAPs) are posited to help Indonesian smallholders, but their real-world adoption and economic efficacy are unverified. A significant gap exists between the technology’s promise and its practical implementation. This study sought to: (1) empirically quantify DFAP adoption rates, (2) rigorously evaluate their economic impact on farm yield and net income, and (3) identify key drivers of adoption. A cross-sectional survey (N=1,240) was conducted in three Indonesian provinces. We employed logistic regression to identify adoption predictors and Propensity The adoption rate was low (25.0%), with a high rejection rate (33.5%). Digital literacy and education were the strongest predictors. The PSM analysis confirmed that adoption yields significant economic benefits, including a 14.2% increase in crop yield and higher net income (p < .01). The findings present a critical paradox: DFAPs are economically effective, but benefits are captured only by a digitally literate “farmer elite.” This “digital divide” mandates a policy shift from technology-centric investment to human-centric interventions focused on digital literacy.